Multicomponent (Ce, Cu, Ni) oxides with cage and core–shell structures: tunable fabrication and enhanced CO oxidation activity. Issue 18 (27th April 2016) - Liu, Wei; Tang, Ke; Lin, Ming; June, Lay Ting Ong; Bai, Shi-Qiang; Young, David James; Li, Xu; Yang, Yan-Zhao; Hor, T. S. Andy
Abstract : Cu2 O cubes from a new formulation have been used as templates to construct hollow and core–shell metal oxide composite structures with enhanced catalytic activity. Abstract : Solvothermal synthesis of Cu2 O cubes from Cu(OAc)2 in ethanol provided templates for tunable formation of novel multicomponent composites: hollow CeO2 –Cu2 O (1 ), core–shell NiO@Cu2 O (2 ) and hollow CeO2 –NiO–Cu2 O (3 ). Composites1–3 catalyze the oxidation of CO at a lower temperature than the parent Cu2 O cubes.